Catalytically Active Amyloids as Future Bionanomaterials - Diaz-Espinoza, R (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Peptides and proteins can aggregate into highly ordered and structured conformations called amyloids. These supramolecular structures generally have convergent features, such as the formation of intermolecular beta sheets, that lead to fibrillary architectures. The resulting fibrils have unique mechanical properties that can be exploited to develop novel nanomaterials. In recent years, sequences of small peptides have been rationally designed to self-assemble into amyloids that catalyze several chemical reactions. These amyloids exhibit reactive surfaces that can mimic the active sites of enzymes. In this review, I provide a state-of-the-art summary of the development of catalytically active amyloids. I will focus especially on catalytic activities mediated by hydrolysis, which are the most studied examples to date, as well as novel types of recently reported activities that promise to expand the possible repertoires. The combination of mechanical properties with catalytic activity in an amyloid scaffold has great potential for the development of future bionanomaterials aimed at specific applications. © 2022 by the author.